2023
DOI: 10.1038/s41467-023-36262-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics and machine learning reveal context-specific gene regulatory activities of PML::RARA in acute promyelocytic leukemia

Abstract: The PML::RARA fusion protein is the hallmark driver of Acute Promyelocytic Leukemia (APL) and disrupts retinoic acid signaling, leading to wide-scale gene expression changes and uncontrolled proliferation of myeloid precursor cells. While known to be recruited to binding sites across the genome, its impact on gene regulation and expression is under-explored. Using integrated multi-omics datasets, we characterize the influence of PML::RARA binding on gene expression and regulation in an inducible PML::RARA cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Nevertheless, the demonstration of the importance of site-specific recruitment by transcription factors in normal physiology is yet to be accomplished. 38 …”
Section: Cancer-related Epigenetic and Dna Methylation Changesmentioning
confidence: 99%
“…Nevertheless, the demonstration of the importance of site-specific recruitment by transcription factors in normal physiology is yet to be accomplished. 38 …”
Section: Cancer-related Epigenetic and Dna Methylation Changesmentioning
confidence: 99%
“…Like RARA, PML-RARA dimerizes with RXR [91,92] and efficiently recruits canonical RAR-RXR co-repressors, such as SMRT or NCOR [93], further increasing its transcriptional repressive activity. Moreover, in APL, PML-RARA also transactivates hundreds of non-canonical RARA target genes, in particular, genes coding for chromatin-modifying enzymes or implicated in cell proliferation [92,[94][95][96][97]. More importantly, deregulation of retinoic acid signaling is essential for the initiation of APL, as RARA fusions are responsible for over 99% of APLs while fusions involving RARB or RARG are very rare occurrences [98].…”
Section: Pml-rara Impairs the Transcriptional Regulation Of Hematopoi...mentioning
confidence: 99%
“…The N-COR transcriptional co-repressor is also associated to PML-RARA, and its SUMOylation, which might be promoted by PML-RARA, favors its transcriptional repressive activities [170,171]. Altogether, the recruitment/modification of PML partner proteins could further control the repression of target genes implicated in hematopoietic differentiation and self-renewal [92,96,97,170,172,173].…”
Section: Recruitment Of Partner Proteins On Pml-raramentioning
confidence: 99%
“…Furthermore, a genome-wide analysis of the PML-RARa/RXR binding site using Chip-seq in an APL cell line (NB4) and primary APL cells revealed that the PML-RARa /RXR dimer interacts with and represses a broader range of promoter regions than its RARa /RXR counterpart [57], likely contributing to the oncogenic action of the fusion protein [55]. The same group and others have also recently demonstrated that PML/RARa exerts transactivating functions through directly binding to target genes such as growth factor independent 1 transcriptional repressor (GFI-1), which is mediated by the recruitment of P300 and HDAC1 and the formation of super-enhancers [58,59]. Additionally, PML-RARa interferes with the formation of PML nuclear bodies, which blunts p53 signaling and leads to the enhanced self-renewal of leukemic cells [60].…”
Section: Disruption Of Retinoid Signaling In Aplmentioning
confidence: 99%